IS SOCIAL-PEDAGOGICAL ASPECTS OF A HEALTHY WAY OF LIFE PUPILS OF KOSTANAY - Bekmukhambetova, L.S.; Ibraeva, R.G. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
In work results research of social and pedagogical monitoring activity of school students of Kostanay concerning sports activity are presented. It is carried out social and pedagogical monitoring which was directed on studying activity of school students concerning sports activity including with use means of physical culture. As technological base for implementation of the project work specially developed questionnaires were chosen and the analysis is carried out. The developed analysis and justification of the importance and relevance of a problem of formation positive the relations of school students to physical culture, as to means of strengthening of health, including with use of results of social and pedagogical monitoring.
Keywords: health; monitoring; sport; physical development; activity